Can the Right Crop Mix Reduce the Water Rebound Effect Following Improvements in Irrigation Efficiency? - Chai, Ying; Zhang, Haoran; Ma, Zilong; Pan, Su; Zhou, Jieqi (Frontiers in Water, 2022)
Water rebound has been recognized as a significant issue that reduces the effectiveness of irrigation efficiency improvement policies aimed at water conservation. However, empirical studies investigating the mechanisms and contexts of water rebound are rare. Thus, in this study, we explore the effects of water rebound on irrigation efficiency improvements from the perspectives of crop mix and climatic region. First, we construct a double-layered moderating effect framework to incorporate the two interactive factors of crop mix and climatic region combined with two rebound mechanisms, cost reduction and increased revenue. Second, we conduct empirical analyses to test three hypotheses based on provincial-level data from 2003 to 2017 in China using pure technology improvement as a proxy for irrigation efficiency. We found that the water rebound effect was about 67.72%. The crop mix had a significant moderating effect on the relationship between irrigation efficiency and water rebound, which is more likely to occur in regions with a higher proportion of grain crops. Crop mixes involving higher proportions of non-grain crops were associated with higher levels of water conservation and less water rebound. Furthermore, non-grain crops in humid regions were more likely to experience water rebound than those in non-humid regions. Thus, given China’s national strategy of food security, reducing the proportion of non-grain crops in humid regions will help to sustain agricultural water resources and conserve the environment.